Band ordering and relativistic effects on HgTe and CdTe electronic structure - Hinostroza Vargas Machuca, Cristhian David (2021)
The topological materials permit transport of polarized charges through edge and surface states in 2D y 3D systems. These edge and surfaces states are protected by topological symmetry order that is based in spin-orbit coupling and in the invariance under time reversal operator.The main purpose of this work is to analyze the evolution of the surface state from HgTe and CdTe alloys observing the band inversion and the effect of d atomic orbital on the band inversion and the spin-orbit coupling intensity.Results where obtained using density functional theory with a local spin density approximation and the Hubbard correction (SLDA+U) considering relativistic effects and spin polarization.